Bone regeneration via skeletal cell lineage plasticity: All hands mobilized for emergencies: Quiescent mature skeletal cells can be activated in response to injury and robustly participate in bone regeneration through cellular plasticity - Matsushita, Yuki; Ono, Wanida; Ono, Noriaki (BioEssays, 2021)
An emerging concept is that quiescent mature skeletal cells provide an important cellular source for bone regeneration. It has long been considered that a small number of resident skeletal stem cells are solely responsible for the remarkable regenerative capacity of adult bones. However, recent in vivo lineage‐tracing studies suggest that all stages of skeletal lineage cells, including dormant pre‐adipocyte‐like stromal cells in the marrow, osteoblast precursor cells on the bone surface and other stem and progenitor cells, are concomitantly recruited to the injury site and collectively participate in regeneration of the damaged skeletal structure. Lineage plasticity appears to play an important role in this process, by which mature skeletal cells can transform their identities into skeletal stem cell‐like cells in response to injury. These highly malleable, long‐living mature skeletal cells, readily available throughout postnatal life, might represent an ideal cellular resource that can be exploited for regenerative medicine.